Pengaruh Lifestyle Dan Kualitas Produk Terhadap Keputusan Pembelian Handphone Iphone Melalui Citra Merek Sebagai Variabel Intervening Studi Kasus pada Generasi Z di Kota Medan - Lafau, Aperius; Chaniago, Sabaruddin; Elanda, Yochi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of lifestyle and product quality on purchasing decisions of iPhone smartphones, with brand image as an intervening variable among Generation Z in Medan City. This study employed a quantitative research method with data collection conducted through the distribution of online questionnaires to 100 Generation Z respondents aged 13–28 years. Data analysis was carried out using The results showed that lifestyle and product quality significantly influence the brand image of iPhone. The lifestyle variable was found to have a significant negative effect on purchasing decisions, while product quality had a positive and significant effect on purchasing decisions. In addition, brand image also had a positive and significant influence on purchasing decisions and acted as an intervening variable in the relationship between lifestyle and product quality toward purchasing decisions. These findings indicate that lifestyle, product quality, and brand image simultaneously play important roles in shaping iPhone purchasing decisions among Generation Z in Medan City.